2019
DOI: 10.1371/journal.pone.0223603
|View full text |Cite
|
Sign up to set email alerts
|

Birth outcomes in women who have taken adalimumab in pregnancy: A prospective cohort study

Abstract: BackgroundInformation is needed on the safety of adalimumab when used in pregnancy for the treatment of certain autoimmune diseases.Methods and findingsBetween 2004 and 2016, the Organization of Teratology Information Specialists Research Center at the University of California San Diego conducted a prospective controlled observational cohort study in 602 pregnant women who had or had not taken adalimumab. Women in the adalimumab-exposed cohort had received at least one dose of the drug in the first trimester f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
37
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 19 publications
(20 reference statements)
9
37
0
4
Order By: Relevance
“…The material included in this quantitative evaluation is shown in Supplementary Figure 1, and Supplementary Tables 1 and 3). Of 116 unique publications identified in this systematic review, including 7941 pregnancies among women with IBD, 5 studies were excluded from the meta-analysis because of a mix of patients with IBD and other chronic inflammatory disorders, including rheumatoid arthritis, [31][32][33][34][35] and 1 other study was omitted because not all participants received a biologic agent. 36 Moreover, all studies with fewer than 10 individuals were excluded from meta-analyses because they often are highly selected (based on a positive or negative findings) and therefore may not be representative of pregnant women with IBD exposed to biologics (Supplementary Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…The material included in this quantitative evaluation is shown in Supplementary Figure 1, and Supplementary Tables 1 and 3). Of 116 unique publications identified in this systematic review, including 7941 pregnancies among women with IBD, 5 studies were excluded from the meta-analysis because of a mix of patients with IBD and other chronic inflammatory disorders, including rheumatoid arthritis, [31][32][33][34][35] and 1 other study was omitted because not all participants received a biologic agent. 36 Moreover, all studies with fewer than 10 individuals were excluded from meta-analyses because they often are highly selected (based on a positive or negative findings) and therefore may not be representative of pregnant women with IBD exposed to biologics (Supplementary Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…The Organization of Teratology Information Specialists (OTIS) analyzed adalimumab in the first trimester of pregnancy in patients with autoimmune conditions and reported a rate of major birth defects of 10% in adalimumab-exposed patients compared with 7.5% in the diseased but unexposed cohort [ 160 ]. OTIS did not report significant increases in structural defects, pregnancy complications, or fetal and infant adverse health outcomes, although the risk of preterm delivery increased [ 160 ]. FDA information showed active placental transfer of adalimumab during the third trimester and a presence in infants for up to 3 months after birth.…”
Section: Comorbid Conditions and Special Populationsmentioning
confidence: 99%
“…A prospective cohort study has concluded that adalimumab is a safe treatment in pregnancy, where clinical benefits of treatment exceed the clinical risks in untreated pregnancies. This study found no increased risk of adverse maternal or foetal outcomes during adalimumab administration [ 178 ].…”
Section: Therapeutic Implicationsmentioning
confidence: 99%